Tragic Consequences of Life in Paulo Coelho’s The Spy: Character Analysis - Wiwin Malinda (Jurnal Indonesia Sosial Sains, 2024)
This study aims to reveal the tragedy experienced by Mata Hari, the main character in Paulo Coelho’s The Spy. Mata Hari struggles to pursue her dreams of independence and luxury, only to face a tragic end. This qualitative research draws from the novel The Spy as the primary source, supported by secondary sources including relevant books and literary analysis. The study focuses on the significant moments in Mata Hari’s life, particularly her marriage to Rudolf MacLeod, which led her to live in Indonesia. Her hopes for a better life were shattered as her husband mistreated her, turning her days in Java into a nightmare. After losing her son, poisoned by his nanny, Mata Hari decided to leave her family and moved to Paris to pursue a life of fame as an exotic dancer. Her fame, however, came with a price, as she was falsely accused of being a spy. Her final days were spent in Saint Lazare prison in Paris before she was executed. The findings of this study demonstrate that the tragic consequences of Mata Hari’s life, shaped by her divorce, fame, and relationships, ultimately led to her demise. Her pursuit of freedom and luxury sealed her tragic fate.